2005
DOI: 10.1086/444503
|View full text |Cite
|
Sign up to set email alerts
|

Slow Clearance of Human Parvovirus B19 Viremia following Acute Infection

Abstract: Parvovirus B19 is a common, clinically significant pathogen. Reassessment of the viral kinetics after acute infection showed that the virus is not rapidly cleared from healthy hosts, despite early resolution of symptoms. These findings challenge our current conception of the virus' pathogenesis and have implications for the management of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
72
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 13 publications
9
72
0
3
Order By: Relevance
“…57 It has been reported that B19V DNA may be detectable by PCR for extended periods of up to years in bone marrow and even serum. 58 Donor-derived nosocomial infection has also been described (blood products; stem cells). 1,59 The infection has been seen in association with other post-transplant complications, such as allograft dysfunction, hepatitis, myocarditis and glomerulonephritis, and post-transplant mortality directly attributable to B19V has been estimated at 3%.…”
Section: Discussionmentioning
confidence: 99%
“…57 It has been reported that B19V DNA may be detectable by PCR for extended periods of up to years in bone marrow and even serum. 58 Donor-derived nosocomial infection has also been described (blood products; stem cells). 1,59 The infection has been seen in association with other post-transplant complications, such as allograft dysfunction, hepatitis, myocarditis and glomerulonephritis, and post-transplant mortality directly attributable to B19V has been estimated at 3%.…”
Section: Discussionmentioning
confidence: 99%
“…First, HBoV is not related to a known human respiratory pathogen. Second, HBoV may be shed persistently, since other human parvoviruses (B19V, PARV4, and the AAVs) have the capacity for asymptomatic persistence (41,44,50). Third, HBoV is commonly detected in association with other respiratory viruses which have an established pathogenic potential.…”
Section: Hbov and Respiratory Tract Diseasementioning
confidence: 99%
“…However, emerging evidence challenges this notion. With the use of sensitive quantitative techniques such as dot blot and nested PCR assays, B19 DNA has been detected in bone marrow and in peripheral blood for months and even years in seemingly immunocompetent individuals, despite the presence of neutralizing antibody (29,30). The clinical significance of this delayed clearance and low-level viremia is unknown.…”
Section: Pathogenesis and Immune Responsementioning
confidence: 99%